PENENTUAN STRUKTUR TANAH SEBAGAI DASAR UJI KELAYAKAN KEKUATAN BANGUNAN PERUMAHAN DI MUARO JAMBI MENGGUNAKAN METODE GEOLISTRIK KONFIGURASI DIPOLE-DIPOLE - Muhammad Ikhsan; Faizar Farid; Samsidar Samsidar; Linda Handayani (Komunikasi Fisika Indonesia, 2018)
This research describes the foundation standard in Muaro Jambi. The objective is to determine the subsurface structure as well as to determine the suitable foundation standards for residential buildings in Muaro Jambi. In this study, data collection is divided into 2 residential places, the first in the housing Arza Griya Mandiri and Griya Sungai Duren Indah housing. Each housing will be taking 3 geolistrik data with path length 160 m and datum point as much as 69 datum. The result of field data obtained in the form of voltage value and current value, this value is inputted into Microsoft Excel software and searched for obstacle value and ρa. Datum point value, space electrode, layer, and value ρa are combined and input into notepad software to be processed using Res2DINV software. The results show that the foundation has been built almost in accordance with soil structure and foundation of soil obtained from the research. A suitable soil layer to build a foundation is a rocky clay layer where in this study the depth of this layer varies from 1.71 m to 18.4 m.